Implementasi Zikir terhadap Pembinaan Akhlak Keseharian Santri di Dayah Kabupaten Aceh Timur - Hayati, Nurul (Tadabbur: Jurnal Peradaban Islam, 2021)
Human is the creation of Allah swt who have morals, potentials, orientations, and tendencies toward positive and negative things. It is a characteristic and moral tied in every human. To neutralize and create a better human which is in accordance with the main purposes of His creator, it needs specific ways to maintain a pure human appearance in their daily life. One of the ways to return and maintain their pureness is through dhikr. It has been implemented by one of the traditional educational institutions in East Aceh, namely the Islamic Boarding School Asasul Islamiyah and the Islamic Boarding School Darul Muta'allimin. In addition, besides teaching a religious subject as the main subject matter, they are also having daily dhikr-routine, before and after praying, and it becomes the main purpose to develop studentsâ€™ morals. This study explores the implementation of dhikr as a development toward Islamic boarding schoolâ€™s studentsâ€™ daily morals in East Aceh regency, with aims (1) To figure out what kind of the several dhikr in the Islamic Boarding School Asasul Islamiyah and Islamic boarding school Darul Muta'allimin, East Aceh regency, (2) To figure out a mechanism of implementing dhikr in the Islamic boarding school Asasul Islamiyah and the Islamic boarding school Darul Muta'allimin, East Aceh, (3) To know an implication dhikr toward daily moralsâ€™ development in Islamic boarding school Asasul Islamiyah and Islamic boarding school Darul Muta'allimin, East Aceh. This present study is qualitative research which is used as a field research method and uses primary and secondary data. The data collection methods used are observations and interviews. The present study found that the varied of dhikr words which are pointed in Islamic boarding school Asasul Islamiyah and Islamic boarding school Darul Muta'allimin, East Aceh Regency is istighfar, tauhid (Ù„Ø§ Ø§Ù„Ù‡ Ø§Ù„Ø§ Ø§Ù„Ù„Ù‡), tasbih, tahlil, shalawat (remembering The Prophet), yassin, reciting Al-Qurâ€™an verses and having a close-by reciting doâ€™a. The mechanisms of implementing dhikr used in both Islamic boarding schools, methodology and time, are similar; using dhikr dzahir and dhikr sirri, in addition, the time is daily; before and after praying. Moreover, one of the dhikr implications toward the studentsâ€™ daily morals development is enhancing Islamic spirituality through remembering Allah SWT in order to form a balancing life between the world and the day after, also have good morals toward humans (habl min al-nÄs) and Allah SWT (habl min AllÄh).